Exploring the Religious Laboratory Tahfiz Program: Enhancing Islamic University Students' Potential - Nurlaila Nurlaila; Yuniar Yuniar; Fajri Ismail; Wasilah Wasilah; Mukti Ali (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to elucidate the characteristics of the Tahfiz program at the Religious Laboratory of the Faculty of Tarbiyah and Teaching Sciences, Raden Fatah State Islamic University of Palembang. Recognizing the importance of structured religious education in higher learning, the research focuses on the program's framework and implementation. Employing a qualitative methodology with a phenomenological approach, data were gathered through purposive sampling, ensuring participants met specific criteria. Techniques such as direct observation, in-depth interviews, and documentation were used for data collection, with analysis following a systematic process of reduction, presentation, and conclusion. The findings reveal that the Tahfiz Al-Qur'an program is meticulously planned, implemented, organized, monitored, and evaluated, significantly enhancing students' memorization skills. Detailed planning stages, rigorous implementation strategies, and organized frameworks for monitoring progress and evaluation are central to the program's success. The structured approach ensures comprehensive development and continuous improvement of students' abilities. The study underscores the effectiveness of the Tahfiz program's systematic framework in nurturing students' memorization skills. It highlights the potential of structured educational initiatives in higher Islamic education to significantly enhance religious scholarship. The well-structured Tahfiz Al-Qur'an program at the Religious Laboratory of Raden Fatah State Islamic University of Palembang plays a crucial role in developing students' potential in memorizing the Al-Qur'an, fostering academic and religious excellence.